Effective hydrogen production by hydrolysis of Mg wastes reprocessed by mechanical milling with iron and graphite - Rodríguez, María Cristina; Urretavizcaya, Guillermina; Bobet, Jean Louis; Castro, Facundo (Elsevier Science SA, 2023)
Fil: Rodríguez, María Cristina. Universidad Nacional de Cuyo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina